BIOSORPSI LOGAM BERAT TIMBAL (Pb) OLEH BAKTERI - Aminah, Ummi; Nur, Fatmawati (Teknosains: Media Informasi Sains dan Teknologi, 2018)
Contamination caused by heavy metals has a high potential of risk because they easily penetrate in to the trofic chain accumulating as organometallic compounds. Lead (II) has been as one of the most toxic heavy metals because it is associated with many health hazards. Therefore, people are increasingly interested in discovering new methods for effectively and economically scavenging lead (II). Recent studies demonstrate biosorption is a promising technology for the treatment of pollutant. Several research demonstrated the ability of lead biosorption by bacteria such as Enterobacter sp, Bacillus sp, Escherichia coli, Micrococcus sp, Aeromonas sp, Lactobacillus sp, and Pseudomonas sp.